Écrire le transfrontalier – voyager en Europe centrale - Radvánszky, Anikó (Verbum – Analecta Neolatina, 2020)
The experience of “transfrontality”, in the concrete and figurative sense of the word, is always strongly dominant in a region where ethnic and national borders have always been separated, in an area where, throughout its history, but especially in the 20th century, in re- and re-emerging units, individual, community, or national identities had to be conceived according to new and new points of reference. The meaning of the concept of Central Europe is very variable, its use is diverse; there are several interpretations of the region based on geographical, political and cultural aspects. It is an indisputable fact that Central Europe today is a literary concept rather than an economic, political and spiritual reality, a concept that is kept alive by writers such as Milosz from Poland, Kundera from the Czech Republic, Miklós Mészöly from Hungary. In my study I compare two literary works, Danubio (Danube) by Claudio Magris and Hahn-Hahn grófnő pillantása (The Glance of Countess Hahn-Hahn) by Péter Esterházy that create and approach the imaginary construction called Central Europe in their own way. Both travel novels capture the trip on the Danube and the experience of transfrontality.